Assessment of cardiovascular fitness among young sedentary adults using 1600 M walking test.: cardiovascular fitness among young sedentary adults - Begum, Aftab; T, Lakshmi; Syed, Sadat Ali (UNUSA Press, 2022)
Background and Objectives: Cardiorespiratory endurance refers to the ability of the heart and lungs to deliver oxygen to working muscles during continuous physical activity, which is an important indicator of physical health. Physical activity is a complex multidimensional behaviour that is difficult to assess in free-living populations and for which a gold standard measurement does not exist. Thereby, we assessed cardiovascular fitness among young sedentary adults using 1600 M walking test Methods: The study participants were assessed for Pulse rate, Respiratory rate, Blood pressure and oxygen saturation at rest followed by 1st, 2nd, 3rd and after 5 minutes after 1600 M walking test. Results: There were no significant changes in pulse rate, respiratory rate, blood pressure; both systolic and diastolic blood pressure, and oxygen saturation across both the genders after performing 1600 M walk at 1st 2nd and 5th minutes except significant changes for respiratory rate (P=0.03) & systolic blood pressure (P =0.02). Conclusion: There is no single gold standard for estimating the cardiac endurance and fitness. It has to be assessed for Vo2 along with basic parameters and need to be repeated to validate the outcome and reduce the bias in case of aerobic exercises.